Splanchnic balance of free fatty acids, endocannabinoids, and lipids in subjects with nonalcoholic fatty liver disease - Westerbacka, J; Kotronen, A; Fielding, B; Wahren, J; Hodson, L; Perttil, J; Seppnenlaakso, T; Suortti, T; Arola, J; Hultcrantz, R; Castillo, S; Olkkonen, V; et al. (2010)
Background and Aims Animal studies suggest that endocannabinoids could contribute to the development of nonalcoholic fatty liver disease (NAFLD). In addition, NAFLD has been shown to be associated with multiple changes in lipid concentrations in liver biopsies. There are no data on splanchnic free fatty acid (FFA), glycerol, ketone body, endocannabinoid, and lipid fluxes in vivo in subjects with NAFLD. Methods We performed hepatic venous catheterization studies in combination with [2H2]palmitate infusion in the fasting state and during a low-dose insulin infusion in 9 subjects with various degrees of hepatic steatosis as determined using liver biopsy. Splanchnic balance of endocannabinoids and individual lipids was determined using ultra performance liquid chromatography coupled to mass spectrometry. Results Concentrations of the endocannabinoid 2-arachidonoylglycerol were higher in arterialized (91 ± 33 μg/L basally) than in hepatic venous (51 ± 19 μg/L; P < .05) plasma. Fasting arterial (r = 0.72; P = .031) and hepatic venous (r = 0.70; P = .037) concentrations of 2-arachidonoylglycerol were related positively to liver fat content. Analysis of fluxes of 85 different triglycerides showed that the fatty liver overproduces saturated triglycerides. In the plasma FFA fraction in the basal state, the relative amounts of palmitoleate and linoleate were lower and those of stearate and oleate were higher in the hepatic vein than in the artery. Absolute concentrations of all nontriglyceride lipids were comparable in arterialized venous plasma and the hepatic vein both in the basal and insulin-stimulated states. Conclusions The human fatty liver takes up 2-arachidonoylglycerol and overproduces triacylglycerols containing saturated fatty acids, which might reflect increased de novo lipogenesis. © 2010 AGA Institute.